Postpartum Depression and Infant Socio-Emotional Development: Systematic Review - Kharisma Nurul Fazrianti Rusman; Raden Roro Ratuningrum Anggorodiputro; Tonny Sundjaya; Ikrimah Nafilata (Universitas Muhammadiyah Semarang, 2026)
Postpartum depression (PPD) is a regularly occurring mental health ailment that may have serious implications for maternal well-being and toddler development. Growing proof suggests that PPD performs a crucial role in shaping the socio-emotional consequences of toddlers for the duration of the early years of life. This systematic literature overview pursuits to synthesize current-day findings on the connection between PPD and toddler socio-emotional development, become aware of research gaps, and highlight implications for practice and policy. Using established choice standards, we analyzed seven peer-reviewed studies published between 2020 until 2025 that examined maternal depressive signs and symptoms and child developmental outcomes. The evaluation discovered regular evidence linking persistent maternal depression with accelerated behavioral problems, reduced emotional variability, and delays in socio-emotional milestones amongst babies and young children. Furthermore, cumulative publicity to each prenatal and postnatal despair is associated with exacerbating developmental risks. While a few studies also explored maternal sleep, parenting stress, and physiological correlates including oxytocin stages, those findings have been much less conclusive. Notwithstanding methodological variation, the reviewed literature supports the urgent need for early identification and intervention for maternal despair to limit lengthy-term negative consequences on kids. Those findings underscore the significance of integrating intellectual health offerings into maternal and child fitness programs and get in touch with for further research on mediating and moderating elements that have an impact on developmental trajectories.